Answer:
Answer is below
Step-by-step explanation:
Add 9 to both sides.
![6b-9+9=-87+9\\6b=-78](https://tex.z-dn.net/?f=6b-9%2B9%3D-87%2B9%5C%5C6b%3D-78)
Divide both sides by 6
![\frac{6b}{6} =\frac{-78}{6} \\b=-13](https://tex.z-dn.net/?f=%5Cfrac%7B6b%7D%7B6%7D%20%3D%5Cfrac%7B-78%7D%7B6%7D%20%5C%5Cb%3D-13)
Answer:
-6 and -3 for the dots
Step-by-step explanation:
hope this is correct im bad at math
Answer:
2.4
Step-by-step explanation:
If you replace m with 7, the expression is now 7-4.6.
7-4.6=2.4
The value of the expression is 2.4.
-hope it helps
<span>x=3y-8
3x-4y=-9
We are told that:
</span>x=3y-8
So replace x in 3x-4y=-9 with x=3y-8 like so:
3(3y-8)-4y=-9
Start by distributing the 3:
![(3)(3y)+(3)(-8)+-4y=-9](https://tex.z-dn.net/?f=%283%29%283y%29%2B%283%29%28-8%29%2B-4y%3D-9)
Now you have:
![9y+-24+-4y=-9 ](https://tex.z-dn.net/?f=9y%2B-24%2B-4y%3D-9%0A)
Combine like terms, now you have:
![5y-24=-9 ](https://tex.z-dn.net/?f=5y-24%3D-9%0A)
add 24 to both sides
![5y-24+24=-9+24 ](https://tex.z-dn.net/?f=5y-24%2B24%3D-9%2B24%0A)
Now you have:
![5y=15](https://tex.z-dn.net/?f=5y%3D15)
Divide both sides by 5 to get:
y=3
Now that you know y=3 plug it into:
x=3y-8
x=3(3)-8
x=1
Final answer: (1,3)